Numerical study of condensing flow based on the modified model. (25th December 2017) - Zhang, Guojie; Zhang, Sen; Zhou, Zhongning; Li, Yimin; Wang, Liang; Liu, Cong
Highlights: The modified model is developed to predict condensation phenomenon. In nozzle, the modified model is more accurate in predicting the Wilson point. The modified model can more accurately predicted the blade surface pressure distribution and flow field characteristic. In the 3-D cascade, with the expansion rate decreasing, the vapor supercooling and the nucleation rate decrease. Abstract: Condensation phenomenon is very common, whether in the steam turbine or refrigeration cycle. This paper firstly numerically studies the Moses and Stein nozzle focusing on condensing flow. Both the modified model and the original model are calculated, besides the results are compared with experimental data to verify the correctness of the numerical simulation based on the error analysis. The results show that the modified model is more accurate than the original model in predicting the Wilson point position and its thermal parameters. Additionally, the pressure will rise due to the release of latent heat in the condensation process, and the nucleation will only occur when the vapor supercooling reaches a certain level, about 18 K. The nucleation rate will reach its maximum when the vapor supercooling reaches maximum, which is defined as Wilson point. In two-dimensional Dykas cascade, the modified model can more accurately predicted the blade surface pressure distribution and flow field characteristic than the original model. Finally, the modified model is applied in three-dimensional steam turbine cascade, and the parameters of flow passage centerline along the spanwise direction are investigated in detail.